The Global Active Citizenship Network in Italian Local Contexts: Using Social Media to Promote Sustainable Behaviours - D’Ambrosi, Lucia (Javnost-The Public, 2017)
The recent increasing presence of environmental movements as forms of spontaneous mobilisation arouses interest about the practices and tools that grow around them. They take place and are created within civic media and are characterised by significant participation in the territory. Starting from these preliminary remarks, this article focuses on analyses of the communication flow between the international network and local nets. The article seeks to understand both the dynamics of such forms of collaboration and how the local identity of Italian partners is structured. Furthermore, this study assesses the role of new media in promoting active networking with its links to global environmental actions and encouraging shared participatory tools. The study highlights interesting connections between global and local events whose intensity depends on innovative ways of using the media and managing Web relationships and networking at national and international levels. Moreover, online activism, at international level, is closely associated with a conscious effort to be transparent and accountable towards local partners. In this regard, social media are functional not only in publishing information about their actions and results, but also in sharing strategies for resolving conflicts and promoting positive change.